2018
DOI: 10.1002/mbo3.574
|View full text |Cite
|
Sign up to set email alerts
|

The effects of low levels of trivalent ions on a standard strain of Escherichia coli (ATCC 11775) in aqueous solutions

Abstract: Considering the ever‐growing usage of trivalent salts in water treatment, for example, lanthanum salts in rare earth, AlCl3 and FeCl3, the effects of different trivalent cations on the bacterium Escherichia coli (E. coli) ATCC 11775 strain have been studied in aqueous solutions. From colony incubation studies, the colony‐forming unit (CFU) densities were found to decrease significantly in the presence of even low levels (10−5 mol/L) of lanthanum chloride. This level of reduction in CFU number is comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Thus, if these ions caused aggregation, the formed aggregates are still small. 55 Here, the metal ion concentrations in the biofilms were much higher (20 mM), and cell aggregation induced by trivalent cations may occur in the biofilms. However, this effect would occur equally for all matrix compositions so that differences between strains must originate from other factors than ion-induced cell aggregation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Thus, if these ions caused aggregation, the formed aggregates are still small. 55 Here, the metal ion concentrations in the biofilms were much higher (20 mM), and cell aggregation induced by trivalent cations may occur in the biofilms. However, this effect would occur equally for all matrix compositions so that differences between strains must originate from other factors than ion-induced cell aggregation.…”
Section: Discussionmentioning
confidence: 84%
“…For planktonic E. coli cells, it was shown that Fe­(III) and Al­(III) in a concentration of 0.01 mM reduce the number of colony forming units by 50% . While it appears likely that biofilms provide protection against heavy metal toxicity, as demonstrated for P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cell agglomerates forming can be explained by the medium's protective response to the metal excess. Also, according to the literature, the presence of di- and trivalent cations reduce electrostatic repulsion, promoting adhesion due to charged layers' shrinkage on the surface ( Deng et al, 2018 ). Results suggest that exometabolite synthesis supports the adaptation of PAB to iron ions ( Inami et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For planktonic E. coli cells, it was shown that Fe(III) and Al(III) in a concentration of 0.01 mM reduce the number of colony forming units by 50 %. 51 While it appears likely that biofilms provide protection against heavy metal toxicity, as demonstrated for P. aeruginosa , 52 it cannot be fully neglected that these cations also have an effect on E. coli cells in biofilms. It is reasonable to assume, however, that the viscoelastic biofilm properties are not significantly altered by the appearance of non-viable bacteria as bacterial cells can most likely be considered as particles in a composite material.…”
Section: Discussionmentioning
confidence: 99%